Developing Students' Mental Health Programs to Create School Well-being and Prevent Juvenile Delinquency - Esterina, Meriam; Sasmita, Ajeng Risnawati; Wijayanti, Rina (Jurnal Gerakan Mengabdi untuk Negeri, 2026)
The understanding of student’s mental health in schools is still limited. The main attention of schools and students tends to be more towards academic and non-academic achievements. Whereas when students are mentally health, they will be able to absorb lessons and understand it easily than those who are less mentally health. Schools and students also need to be aware of the negative impacts of juvenile delinquency behavior so they could prevent this behavior from occurring, both in school and society. The importance of student mental health program is not only applicable in Indonesia, but also in other countries. Based on preliminary study conducted at schools in Thailand, information obtained that there was a feeling of pressure in carrying out activities at school and there was concern about juvenile delinquency behavior. This international community service activity was carried out to help overcome the problems faced by schools in Thailand. The development of student mental health programs in schools is important to create school well-being and prevent juvenile delinquency behavior. This community service activity was attended by 40 participants consisting of teachers and students from Sangkhom Islam Wittaya School Thailand. The community service activity programs were in the form of education on adolescent mental health programs and prevention of juvenile delinquency. The results of this activity showed that students increasingly understand the importance of developing things that can maintain their mental health. Teachers have knowledge about factors that could improve students' mental health and preventive efforts to prevent juvenile delinquency in schools.